Unraveling the Collapse of Private Sector Banks in India : Evidence from the Lakshmi Vilas Bank’s Financial Performance - Bhatia, Ananya; Kumar, Jagdeep (Indian Journal of Finance, 2024)
Purpose : The banking sector faced a significant jolt when the RBI merged Lakshmi Vilas Bank (LVB) with the Development Bank of India Ltd. (DBIL). Thus, this study aimed to analyze the financial performance of LVB to understand the reasons that led to its collapse. Additionally, this study aimed to evaluate the current financial performance of the DBIL to examine the post-merger effects on the bank. Methodology : The study delved into a comprehensive 10-year analysis of LVB’s financial performance, stretching from 2011 to 2020, employing trend analysis, common-size balance sheets, and financial ratios to find out the reasons that led to the failure of the LVB bank. Findings : The study, in particular, showed that LVB was facing the issue of asset-liability mismatch, which led to increased non-performing assets (NPAs), declining asset quality, weak corporate governance, unsound lending practices, and insufficient regulatory oversight. Moreover, the data suggested that the merger significantly impacted DBIL’s financial performance, with improvements in return on assets and return on equity but challenges like increased gross and net NPA and a decline in business and profit per employee ratios. Practicality : Moreover, this study would contribute to the existing body of knowledge by providing a detailed case study of LVB, offering insights into the specific causes of its failure. It will also suggest policy implications for preventing similar occurrences in the future and enhancing the stability of the Indian banking sector. Originality : This study’s uniqueness lies in its potential to identify measures that could prevent similar failures in the future.